2018
DOI: 10.17116/jnevro201811810193
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of brain peptide-containing drugs: cortexin

Abstract: ФГБУН «Институт высшей нервной деятельности и нейрофизиологии» РАН, Москва, Россия; ГБУЗ «Научно-практический психоневрологический центр им. З.П. Соловьева» Департамента здравоохранения Москвы, Москва, Россия В статье рассмотрены новые данные, касающиеся ключевых молекулярных механизмов, которые могут лежать в основе нейропротективных свойств многокомпонентных лекарственных органоспецифичных препаратов, представляющих собой выделенные из мозга животных пептидные гидролизаты. Такие препараты, в том числе кортек… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Neuron-specifi c protein 14-3-3 is a signal transduction factor ("molecular switch"), particularly modulating neuron death. Cytoskeleton proteins (tubulin and actin) also support the normal functioning and integrity of neurons and other brain cells; impairments to their structure are accompanied by cell death [53].…”
Section: Mechanisms Of Nervous System Changes In Covid-19 Penetration...mentioning
confidence: 99%
“…Neuron-specifi c protein 14-3-3 is a signal transduction factor ("molecular switch"), particularly modulating neuron death. Cytoskeleton proteins (tubulin and actin) also support the normal functioning and integrity of neurons and other brain cells; impairments to their structure are accompanied by cell death [53].…”
Section: Mechanisms Of Nervous System Changes In Covid-19 Penetration...mentioning
confidence: 99%
“…The advantage of these compounds over other neuroprotectors is the lack of immunogenicity and a wide spectrum of action. It has been shown that ultrashort peptides are involved in the regulation of cell differentiation, apoptosis, and proliferation [10] and also have a neuroprotective effect in in vitro and in vivo AD models [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%